(untitled) (REMUNOM, 2026)
The objective was to investigate the measurement instruments used to assess the motor development of children and adolescents and the characteristics of the environment. The study was bibliographic. The data search was conducted in the CAPES Periodicals Portal, using the term "motor development," with articles gathered between 2020 and 2024, resulting in 15 articles for analysis. The most frequently used measurement instruments in the articles were the Test of Gross Motor Development - Second Edition (TGMD-2) and the Rosa Neto Motor Development Scale (EDM), each cited in five articles. The most frequently trained environment was the school. It is concluded that measurement instruments are important tools for assessing students’ motor development, serving as indicators of possible motor delays and providing a basis for teachers to develop activities in the school environment.